Suco desidratado de caju (Anacardium occidentale L.) por atomização: caracterização físico-química, bioativa e estudo da vida de prateleira do produto - Moraes, Francisca Pereira de (2014)
Despite the relatively organized cashew (Anacardium occidentale L.) productive chain and the number of cashew derivatives found in the market, it is estimated that over 90% of the cashew peduncle is wasted. A possible strategy for a better commercial exploitation of this agroindustrial commodity would be the production of spray dried cashew pulp. Thus, this paper approaches the yellow cashew pulp spray drying process and the final product evaluation. Based on that, the shelf life of the spray dried cashew pulp packed in different packaging was evaluated. Drying was conducted in two drying temperatures (140 °C to 150 °C) and two concentrations of Arabic gum (AG, 15% and 25%), which summed four experimental groups. The drying performance was evaluated as well as the physicochemical characteristics (moisture, water activity, total soluble solids, pH, density, solubility, particle diameter, hygroscopicity, degree of caking, color, scanning electronic microscopy and X-ray diffraction), composition (protein, ash, fat and sugars) and bioactive and functional value (total phenolic compounds, carotenoids, ascorbic acid and antioxidant activity) of the final products. Results showed spray drying efficiency higher than 65% for all experiments, mainly for the C4 group (150 °C and 25% AG) which reached efficiency of 93.4%. It was also observed high solubility (94.7% to 97.9%) and the groups with lower hygroscopicity (5.8% and 6.5%) were those with the highest proportion of drying coadjuvant. The particle diameters ranged between 14.7 μm and 30.2 μm and increased with the proportion of AG. When comparing the product before and after spray drying, the drying impact was evident. However, despite the observed losses, dried yellow cashew showed high phenolic concentration (from 235.9 to 380.4 mg GAE eq / 100 g DM), carotenoids between 0.22 and 0.49 mg/100 g DM and remarkable ascorbic acid levels (852.4 to 1346.2 mg/100 g DM), in addition to antioxidant activity ranging from 12.9 to 16.4 μmol TE/ g DM. The shelf life study revealed decreased phenolic content over time associated to a slight water activity increase. Overall, our results unveil the technological and bioactive potential of dried yellow cashew as a functional ingredient to be used in food formulations or as a ready-to-use product. The technological approach presented here can serve as an efficient strategy for a rational use of the cashew apple, avoiding its current underutilization